Private University Management: default risk by students - Freitas Ribeiro, Cristiane; Zani, João; Macagnan, Clea Beatriz; Mesquita Zanini, Francisco Antonio (Review of Business Management, 2012)
This paper analyzes the probability of default risk in a private university (UP) using the statistical technique of logistic regression. The credit risk model used was based on a sample of registered UP students in Rio Grande do Sul. The explanatory variables of the model were obtained by applying a socioeconomic questionnaire that generated a total of 59 variables, of which only three were representative: the existence of debits that had already been negotiated, credit card ownership and rejection. The obtained results show that the studied model yields satisfactory results when used to measure credit risk probability. Key words: Private university. Risk. Default.